Nanomechanical interlocking mechanism of 10-MDP nanolayering - Mohammed H. Ahmed; Daniel Arenas Esteban; Nina Attik; Mohammed M. Awad (Scientific Reports)
Abstract The functional monomer 10-methacryloyloxydecyl dihydrogen phosphate (10-MDP) and its calcium salt (Ca-MDP), formed via interfacial nanolayering, are critical for achieving long-term dental bonding durability. Despite extensive clinical use, the crystallinity, three-dimensional (3D) organization, and hierarchical ultrastructure of Ca-MDP remain inadequately characterized at the nanometric scale. This study aims to investigate the crystallinity, structural nature of Ca-MDP salt and their potential role in the durability of 10-MDP-based adhesives. Three characteristic diffraction maxima corresponding to Ca-MDP nanolayers were initially detected using powder X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM). However, further high-resolution analysis via advanced STEM techniques—including High-Angle Annular Dark Field (HAADF), rotationally invariant Center of Mass (riCOM), and integrated Differential Phase Contrast (iDPC)—revealed that the Ca-MDP salt does not exhibit atomic crystallinity but rather forms a layer-ordered amorphous architecture. The Ca²⁺-rich nanolayers demonstrated variable interspacing and lacked definitive lattice fringes typically associated with crystalline phases. Electron tomography further confirmed a nonuniform, anisotropic self-assembly across X, Y, and Z axes, resulting in 3D directional spreading and spatially distinct nanolayered domains. These findings support a novel nanomechanical interlocking hypothesis: during clinical bonding procedures, adhesive resin components are physically entrapped within the Ca-MDP inter-nanolayers—contributing to enhanced durability. This study proposes a new 3D structural model of Ca-MDP self-assembly, offering deeper mechanistic insights into the long-term performance of 10-MDP-containing adhesives.